Pengembangan Lembar Kerja Peserta Didik berbasis pendekatan open ended dengan konteks kearifan lokal - Kharisma, Intan; Hartatiana , Hartatiana; Wardani, Ambarsari Kusuma (Universitas Mercu Buana Yogyakarta, 2023)
The ability that receives considerable attention from the field of education is the ability to think creatively. This research aims to produce teaching materials in the form of worksheets for mathematics students based on an open ended approach with a valid and practical local wisdom context. The research method used is the development research method which has 2 stages, namely using the formative evaluation model from Tessmer (1998). The first stage is the preliminary stage (preparation and design stage) and the second stage is the formative evaluation stage (self evaluation, expert review, one-to-one, small group, and field test). The sample in the study was 23 students in grade VIII. Data collection was carried out using validation sheets, questionnaires, interviews, and documentation. The results of the research are in the form of worksheets for mathematics students based on the open ended approach with a valid local wisdom context based on the comments and suggestions provided by the validator and declared valid by the expert team at the expert review stage and produce a mathematical LKPD based on an open ended approach with a practical local wisdom context according to the calculation of the student response questionnaire in the one-to-one phase, small group, and field test. The results of validation by experts showed a validity rate of 85.9, while the practicality level of the trial reached 82.2.